2015
DOI: 10.1007/s13277-015-3607-8
|View full text |Cite
|
Sign up to set email alerts
|

Serum DLK1 is a potential prognostic biomarker in patients with hepatocellular carcinoma

Abstract: Hepatocellular carcinoma (HCC) is the sixth most prevalent cancer and the third most frequent cause of cancer-related death in developing countries, especially in East Asia and South Africa, and the identification of new biomarkers for early diagnosis and prognosis is needed. Delta-like 1 homologue (Drosophila) (DLK1) is expressed in malignancies and promotes cancer cell stemness and tumourigenicity, which makes this molecule a potential target for therapies directed against cancer stem/progenitor cells. Here,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
(53 reference statements)
0
14
1
Order By: Relevance
“…Our previous study also indicated that DLK1 was overexpressed in 73.2% human HCC specimens because of the decreased DNA methylation on the promoter of DLK1 [19]. A recent study demonstrated serum DLK1 is a potential prognostic biomarker in HCC patients [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also indicated that DLK1 was overexpressed in 73.2% human HCC specimens because of the decreased DNA methylation on the promoter of DLK1 [19]. A recent study demonstrated serum DLK1 is a potential prognostic biomarker in HCC patients [26]. …”
Section: Discussionmentioning
confidence: 99%
“…Delta-like 1 homolog is expressed in malignancy and promotes cancer cell stemness and tumorigenicity so it can be used as therapeutic target and tumor marker for cancer stem/progenitor cells. Li et al (2015) revealed that tumor size of HCC was positively correlated to DLK1 in serum. DLK1 can be a complement to Alpha Feto Protein (AFP) in the diagnosis of HCC (Li et al, 2015;Chauhan and Lahiri 2016;Shen et al, 2016).…”
Section: Dlk1 As Hepatocellular Carcinoma Markermentioning
confidence: 96%
“…Huang et al [154] demonstrated that proliferation of SMMC-7721 cells was significantly enhanced by exogenous DLK1, whereas colony-forming ability, cell growth, and tumorigenicity of Huh-7, Hep3B, and HepG2 cells were significantly impeded by the suppression of endogenetic DLK 1 via RNA interference. It was identified by Li et al [13] that the enhancing effect of DLK1 in tumourigenicity and cancer stemness could potentially be used as a molecule target for therapies against LCSCs. DLK1+ cells have been discovered in all 17 HCC cell lines and showed a more potent capability of clonogenicity in vitro and tumorigenicity in animal models.…”
Section: Dlk1mentioning
confidence: 99%
“…In order to develop patient-specific therapies that target LCSCs, multiple stemness surface markers have been identified consisting CD133 [2] , CD44 [3] , CD90 [4] , epithelial cell adhesion molecule (EpCAM) [5] , CD47 [6] , CD34 [7] , C-kit [8] , CD13 [9] , CD24 [10] , calcium channel α2δ 1 isoform5 [11] , oval cell marker OV6 [12] , DLK1 [13] , K19 [14] , and Lgr5+ [15] [ Table 1]. The integrated therapy using conventional anti-carcinogenic inhibitors such as sorafenib with LCSCs-targeting drugs, may provide an effective therapeutic strategy for complete elimination of liver cancer.…”
Section: Introductionmentioning
confidence: 99%